Onion quality and yield after agronomic biofortification with selenium - Machado, Beliza Queiroz Vieira [UNESP]; de Jesus Pereira, Breno [UNESP]; Rezende, Gabriel Fernandes [UNESP]; Filho, Arthur Bernardes Cecílio [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2024)
The hidden hunger for Se in the world population is well known. As a strategy to address this issue, this study aimed to biofortify onion (Allium cepa L.), since it is a condiment vegetable consumed by different economic classes and is widely used in the food industry. To this end, Se doses (0, 10, 25, 50, 100 and 200 g ha-1) and application forms (soil and foliar) were evaluated on the biofortification of the bulb and crop yield. The Se source was sodium selenate. Via soil, Se was applied together with NPK fertilizer in the pre-transplantation of the seedlings. Via foliar application, Se was sprayed 77 d after seedlings were transplanted. The Se increased yield up to 99 g ha-1, which was 14.7% higher than the yield obtained in the crop not fertilized with Se. Foliar application of Se was more efficient than soil application in the biofortification of onion, although both were effective. With the dose that promoted the highest yield, the Se concentrations reached 0.487 and 0.317 mg Se kg-1 in onion dry mass, when the supply was made via foliar and soil applications, respectively. The increase in Se supply did not influence bulb quality, as demonstrated by the macro-and micronutrients content and pungency.
Keywords: Allium cepa; biofortified industrial condiment; nutritional deficiency; sodium selenate